Zionism, Translation and the Politics of Erasure. - Gordon, N. (Political Studies, 2002)
This paper examines the translation of classic political philosophy into Hebrew, arguing that a variety of ideological positions can be disclosed simply by examining the erasure process employed during translation. Exploring the connection between translation and nation–building, I claim that segments from John Stuart Mill’s On Liberty, John Locke’s Two Treaties of Government and Thomas Hobbes’s Leviathan were excised in the service of a Zionist identity politics. Insofar as Zionism is a discursive formation, its production and maintenance involves the expulsion of components that may hinder the fabrication of a unified identity. Counter–narratives of the nation that disrupt its totalizing boundaries may disturb, in Homi Bhabha’s words, ‘those ideological maneuvers through which “imagined communities” are given essentialist identities’. By way of conclusion, I argue that the altered texts are in effect a sign that one ideology overpowered another and led, as it were, to the corruption of the spirit underlying the original project of translating classics into Hebrew, a project that was initiated by Leon Roth for different ideological reasons.